(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article explores the challenges that arise when translating proverbs between Uzbek and English. Proverbs, as a key element of a language’s cultural heritage, often prove difficult to translate due to linguistic and cultural differences. Through a comparative analysis of Uzbek and English proverbs, this study identifies common translation problems, such as non- equivalence, cultural gaps, and stylistic disparities.